Effects of neem leaf extract and hot water treatments on shelf life and quality of banana: Effect of plant extract and hot water on banana (Journal of the Bangladesh Agricultural University, 2018)
A huge loss of banana occurs due to its shorter shelf life and inappropriate postharvest handling. There is a scarce of effective postharvest practices to combat this situation in Bangladesh. In this context, the current experiment was conducted to assess the effects of hot water (45°C for 2 or 5 minutes) and neem leaf extract (20% or 40%) on quality and shelf life of banana (cv. Sabri). The experiment was carried out in completely randomized design with three replications. Data on physico-chemical properties of banana were collected during storage in ambient conditions for two weeks. After two weeks of storage, the banana treated with 40% neem leaf extract showed longest shelf life (8.33 days), minimum change in color (score 4.88), minimum disease incidence (33.33%) and severity (score 2.23), lower reduction of titratable acidity (0.12%) and lower level of total soluble solid (6.90%). While the banana were treated with hot water at 45°C for 2 min, the treated banana also showed lower color change (score 4.53), longer shelf life (8.33 days), minimum loss of firmness (score 4.67), minimum change in vitamin C content (2.17mg/100g) and lower reduction in titratable acidity (0.11%). Among the combined treatments, the banana treated with the combination of hot water (at 45°C for 5 minutes)and 40% neem leaf extract also exhibited considerably longer shelf life (8.17 days), lower change in color (score 5.00), lower disease incidence (46.67%) and lower reduction in titratable acidity (0.15%). From the study it could be concluded that the fruit treated with 40% neem leaf extract retained the majority of the quality parameters for considerably longer period and thereby it could be recommended for practical use to ensure better and longer storage of banana (cv. Sabri)J.Bangladesh Agril. Univ. 16(3): 351–356, December 2018